Preliminary study: 3D game on personalized wilderness adventure - Khairol Salleh, Putery Nuralleysa Dania; Mat Zain, Nurul Hidayah; Abdul Aziz, Azlan (College of Computing, Informatics, and Mathematics, 2025)
Survival in the bush was once essential for existence, requiring children to learn survival skills at a young age. These skills, while less commonly needed today, remain valuable for emergencies and everyday challenges. However, traditional methods of teaching these skills make it hard to engage learners due to a lack of enjoyment and relevance. There is a pressing need for personalized gamification to teach youth about nature and survival techniques effectively. This preliminary study investigates the impact of personalized gamification elements on learning survival skills. The study aims to understand the participants’ preferences and the effectiveness of gamified learning. An online survey was distributed via social media platforms, gathering data from 30 respondents aged between 18 and 25 years. The survey comprised two main sections: demographic information and user perceptions regarding personalized gamification and traditional learning methods. The findings reveal that 93.3% of respondents have experience playing survival games, yet over half are unfamiliar with personalized gamification elements. This data underscores the potential for personalized gamification strategies to enhance the enjoyment and learning of survival skills through games.